Java GUI aplication for comparing the levels of biometric security - fingerprint vs. iris - Lalović, Komlen G.; Bogdanoski, Mitko Z. (Vojnotehnički glasnik / Military Technical Courier, 2021)
Introduction/purpose: The main purpose of this paper is to present a novel Java GUI – based software application for a comparative analysis of fingerprint and iris biometrics. Methods: The first part of this work is realized in Java Programming language. in the GUI framework named swing while the rest of the paper shows in detail the advantages and disadvantages of both systems and gives scientific data on when fingerorint and iris recognition can be used to enable top level security. The main method here is a well known comparative analysis. Results: The results were obtained for both fingerprint and iris biometrics, showing the difference between the two. Conclusion: Different types of biometrics, based on body parts formed at different age, are given as well as the comparison of their security levels.